Plukenetia volubilis leaves as source of anti-Helicobacter pylori agents - Tan, Aditya; Scortecci, Katia Castanho; Cabral De Medeiros, Nathalia Maira; Kukula-Koch, Wirginia; Butler, Thomas J.; Smith, Sinéad Marian; Boylan, Fabio (Frontiers in Pharmacology, 2024)
This piece of work showcases the plant Plukenetia volubilis as a source of pharmacologically active polyphenols. These compounds were identified by High-Performance Liquid Chromatography coupled to Electrospray Ionisation and Quadrupole Time-of-Flight Mass Spectrometry (HPLC-ESI-QTOF-MS-MS) analysis of its water infusion. HSCCC from the ethyl acetate extract of the water infusion allowed for the separation and structure characterisation of Astragalin. In vitro testing with the water extract, the ethyl acetate extract and Astragalin demonstrated the anti-Helicobacter pylori activity using a clarithromycin-resistant clinical isolate (MIC = 0.53, 0.51 qnd 0.49 µg/mL, respectively). Moreover in-silico analysis for astragalin confirmed its strong interactions with target proteins for H. pylori.